Left atrial strain predicts hemodynamic parameters in cardiovascular patients. Issue 8 (29th June 2017) - Hewing, Bernd; Theres, Lena; Spethmann, Sebastian; Stangl, Karl; Dreger, Henryk; Knebel, Fabian
Abstract : Background: We aimed to evaluate the predictive value of left atrial (LA) reservoir, conduit, and contractile function parameters as assessed by speckle tracking echocardiography (STE) for invasively measured hemodynamic parameters in a patient cohort with myocardial and valvular diseases. Methods: Sixty‐nine patients undergoing invasive hemodynamic assessment were enrolled into the study. Invasive hemodynamic parameters were obtained by left and right heart catheterization. Transthoracic echocardiography assessment of LA reservoir, conduit, and contractile function was performed by STE. Results: Forty‐nine patients had sinus rhythm (SR) and 20 patients had permanent atrial fibrillation (AF). AF patients had significantly reduced LA reservoir function compared to SR patients. In patients with SR, LA reservoir, conduit, and contractile function inversely correlated with pulmonary capillary wedge pressure (PCWP), left ventricular end‐diastolic pressure, and mean pulmonary artery pressure (PAP), and showed a moderate association with cardiac index. In AF patients, there were no significant correlations between LA reservoir function and invasively obtained hemodynamic parameters. In SR patients, LA contractile function with a cutoff value of 16.0% had the highest diagnostic accuracy (area under the curve, AUC: 0.895) to predict PCWP ≥18 mm Hg compared to the weaker diagnostic accuracy of average E/Eʹ ratio with an AUC of 0.786 at a cutoff value of 14.3. In multivariate analysis, LA contractile function remained significantly associated with PCWP ≥18 mm Hg. Conclusion: In a cohort of patients with a broad spectrum of cardiovascular diseases LA strain shows a valuable prediction of hemodynamic parameters, specifically LV filling pressures, in the presence of SR.